The impact of social sustainability awareness and green trust on consumer buying behavior - Fang, Yu Mei (2024)
This study examines the impact of social sustainability awareness and green trust on consumer purchasing behavior in Malaysia, a country that is increasingly aligning with the global agenda of promoting sustainable consumption. Grounded in stakeholder theory and supported by an extensive review of existing literature, this research explores two pivotal relationships: the impact of social sustainability awareness and green trust on consumer behavior. The role of green trust as a critical determinant in shaping sustainable purchasing patterns. These relationships are analyzed to understand how consumers prioritize ethical and environmentally conscious choices in their decision-making processes.